Північно-східна ділянка городища літописного Бужська - Довгань, П.М. (Археологія і давня історія України, 2010)
В статті висвітлюються топографічні, історичні аспекти та особливості культурного шару північно-східної частини городища літописного Бужська. В основу лягли матеріали з розкопок, які проводились тут експедицією Інституту археології ЛНУ ім. І. Франка у 2004, 2007—2008 рр. Особливий наголос зроблено на результатах розкопок 2008 р. Освещаются топографические, исторические аспекты и особенности культурного слоя северо-восточной части городища летописного Бужска. В основу легли материалы из раскопок, которые проводились здесь экспедицией Института археологии ЛНУ им. И. Франко в 2004, 2007—2008 гг. Особый акцент сделан на результатах раскопок в 2008 г., когда было исследовано редкие наземные и углублённые жилищные и хозяйственные сооружения Х—ХІІ в., обнаружены коллекции изделий из кости, рога и стекла. Среди них — берестяной свёрток Х в., берестяной свиток ХІІ в., костяное писало и шахматная фигурка с буквами. The article enlightens some topographic and historical aspects as well as specific features of cultural layers found in the north-eastern part of Ancient Buzhs’k Hillfort. It is based on the materials from excavations which were conducted by the expedition of the Institute of Archaeology of Ivan Franko L’viv National University in 2004, 2007—2008. Special attention is paid to the results of excavations of the year 2008. These excavations uncovered rare on-ground and under-ground dwellings as well as the house-keeping structures dated of 10th—12th centuries. The collections of bone goods, horn goods, and glass artifacts are found. They include elm roll of 10th century, elm scroll of 12th century, bone pen and chess figure with inscribed letters.